2009
DOI: 10.1002/xrs.1215
|View full text |Cite
|
Sign up to set email alerts
|

Applications of the ‘CATGIXRF’ computer program to the grazing incidence X‐ray fluorescence and X‐ray reflectivity characterization of thin films and surfaces

Abstract: Grazing incidence x‐ray fluorescence (GIXRF) analysis technique has the potential of being one of the most powerful and versatile methods for characterization of layered materials, as it combines features of both x‐ray reflectivity (XRR) and x‐ray fluorescence techniques. GIXRF technique allows non‐destructive evaluation of layer thickness, interface roughness, interlayer formation and depth profiling for an impurity element inside a layer medium or in the substrates. A computer program ‘CATGIXRF’, has been de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…It was found that in single layer sample the normalized angular dependences of emission intensities of Mn and Fe are shifted one with respect to the other by value of ∼0.01°. This fact is interpreted as an increase of the Mn content toward the surface of the film [13]. In the sample with Ta layer, such shift of the emission intensities of Mn and Fe was not detected, indicating homogeneity of the chemical composition through the thickness of the film.…”
Section: Resultsmentioning
confidence: 88%
“…It was found that in single layer sample the normalized angular dependences of emission intensities of Mn and Fe are shifted one with respect to the other by value of ∼0.01°. This fact is interpreted as an increase of the Mn content toward the surface of the film [13]. In the sample with Ta layer, such shift of the emission intensities of Mn and Fe was not detected, indicating homogeneity of the chemical composition through the thickness of the film.…”
Section: Resultsmentioning
confidence: 88%
“…6, 7 GIXRF attracts new attention nowadays, as technologically highly relevant materials with thicknesses of few nanometres are now manufactured. In 2010, Tiwari et al 8 published the application of combined XRR and GIXRF measurements for the investigation of thin films and multilayered materials.…”
Section: Introductionmentioning
confidence: 99%
“…The calculation of the angular dependence of an X-ray fluorescence line on the emission angle can be realized by means of the reciprocity theorem to derive the angular profile from GIXRF calculations [97] or by starting from a matrix formalism to simulate the propagation of an electromagnetic wave through a stratified medium [98,99]. In inverse modeling or forward calculation approaches, which are commonly used for measurements in grazing incidence, the disturbed X-ray wave-pattern has to be accounted for: in an iterative procedure, a model for the (a priori unknown) sample has to be assumed in order to calculate a standing wave-pattern [100] which allows to reproduce the experimental data, then the model is optimized.…”
Section: Analysis Methodologymentioning
confidence: 99%